Le principe de solidarité écologique : une avancée pour le droit de la biodiversité ? - Simon Jolivet (VertigO)
The principle of ecological solidarity should allow for the creation of new links: spatial, temporal and between living beings. This paper assesses its contribution to its historical field of appearance, the biodiversity law. In protected areas law, and more broadly in the territorial dimension of biodiversity law, ecological solidarity appears to be fairly well established conceptually, even if its implementation remains largely perfectible. Initially limited by the law to national parks, the logic of ecological solidarity has been implicitly extended to the law of nature reserves by the administrative judge. Moreover, the ecological continuities of the green and blue belt should make it possible to extend ecological solidarity to the rest of the national territory, outside protected areas, and to add a temporal dynamic to it. On the other hand, species protection law paradoxically appears to be lagging behind in the institution of the logic of ecological solidarity. This is illustrated in particular by the policies of "regulation" of wild fauna, which often neglect the interdependencies between living beings while transcending legal statuses ("pest" species, protected species, etc.). Ways are suggested to remedy this, such as the synergy of the principle of ecological solidarity with other principles of environmental law, in particular the precautionary principle.